2021
DOI: 10.3390/metabo11010030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Detoxification of 2-Oxobutyrate by Remodeling Escherichia coli Acetate Bypass

Abstract: 2-Oxobutyrate (2-OBA), as a toxic metabolic intermediate, generally arrests the cell growth of most microorganisms and blocks the biosynthesis of target metabolites. In this study, we demonstrated that using the acetate bypass to replace the pyruvate dehydrogenase complex (PDHc) in Escherichia coli could recharge the intracellular acetyl-CoA pool to alleviate the metabolic toxicity of 2-OBA. Furthermore, based on the crystal structure of pyruvate oxidase (PoxB), two candidate residues in the substrate-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As expected, we observed a decrease in 2-aminobutyrate and an increase in 2KB compared to that of SYN12 ( Figure 3B ). Because 2KB is directly upstream of 1-propanol, the decrease in 1-propanol titer is counterintuitive, and may be a result of 2KB toxicity ( Zhang et al, 2016 ; Fang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, we observed a decrease in 2-aminobutyrate and an increase in 2KB compared to that of SYN12 ( Figure 3B ). Because 2KB is directly upstream of 1-propanol, the decrease in 1-propanol titer is counterintuitive, and may be a result of 2KB toxicity ( Zhang et al, 2016 ; Fang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As an indispensable metabolic intermediate in biological metabolism, 2-KB is found in the biosynthesis of L-isoleucine ( Park et al, 2012 ; Yin et al, 2012 ), 2-aminobutyrate ( Xu et al, 2019 ), 1-butanol ( Atsumi and Liao, 2008 ), L-homoalanine ( Zhang et al, 2010 ), and so on. However, because of its structural similarity with pyruvate, 2KB competitively inhibits enzymes used in pyruvate metabolism at high concentrations, which causes cellular toxicity ( Zhang et al, 2016 ; Fang et al, 2021 ). As such, this suggests that enhancing the turnover rate of 2-KB to 1-propanol with KivD and YqhD may relieve toxicity caused by 2KB accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of four genes involved in threonine biosynthesis from L-aspartate, hom, thrB, thrC , and thrD , may involve enhanced threonine biosynthesis in MRSA under NaP treatment. Synthesized threonine can then be converted into glycine and serine and, subsequently, pyruvate for energy or into isoleucine ( Fang et al, 2021 ). During the conversion, ilvA is responsible for conversion of serine to pyruvate and, together with sdaAB , the conversion of threonine into 2-oxobutyrate (2-OBA), a precursor metabolite of isoleucine.…”
Section: Discussionmentioning
confidence: 99%
“…However, NaP did not affect the gene expression of enzymes involved in conversion of threonine into glycine or of glycine into serine, suggesting that NaP-induced ilvA expression is involved in 2-OBA generation. Of note, 2-OBA is a toxic metabolic intermediate leading to the arrest of cell growth in most microorganisms ( LaRossa et al, 1987 ; Fang et al, 2021 ). Thus, NaP-induced ilvA expression following up-regulated threonine biosynthesis may suppress MRSA growth by excessive 2-OBA production.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results of both transcriptome and metabolome analyses showed that propanoate metabolism pathways were induced by sewage treatment and key genes related to propanoate metabolism (Table S5). Furthermore, the downregulated metabolite was 2-oxobutanoate (2-OBA), which as a toxic metabolic intermediate, generally arrests the cell growth of most microorganisms and blocks the biosynthesis of target metabolites [35-36]. In the wastewater treatment process, the metabolite of 2-OBA is downregulated, which can promote the effect of microalgae on wastewater treatment and maintain the normal metabolism of microalgae.…”
Section: Discussionmentioning
confidence: 99%